Association of the rs1801133 and rs1801131 polymorphisms in the MTHFR gene and the adverse drug reaction of methotrexate treatment in a sample of Iraqi rheumatoid arthritis patients - Qassim Mahdi Mutlak; Ali Abdulhussain Kasim (Pensoft Publishers, 2024)
Background: Methotrexate is one of the mainstays for treating rheumatoid arthritis (RA) with a wide range of adverse drug reactions, however, it's the relationship between adverse drug reactions and genetic polymorphism remains to be highlighted, and there is a lack of studies concerning Arabic Iraqi population regarding this aspect. Objective: Evaluate the association between genetic mutations in the MTHFR gene in SNPs (rs1801133G>A and rs1801131T>G) on the adverse drug reaction for RA Iraqi patients. Methods: An observational study, that involved 95 Iraqi RA patients with established RA. Patients were divided according to the occurrence of adverse drug reactions. A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was being utilized for MTHFR variants (rs1801133 and rs1801131). The Macrogen Company (Korea) provided the forward and reverse primers in lyophilized form. All PCR procedures are carried out using a PCR thermal cycler (Germany). Results: The study included 95 patients with RA, with a mean age of 43.1 ± 10.6 years, most of the patients were female (85.3%), about 35.8% were smokers, most of the patients had disease low activity (45.2%), followed by moderate (41.1%), high (9.5%), and remission (4.2%). No significant association between individual genetic polymorphism with adverse drug reactions. AG haplotype for rs1801133 rs1801131 polymorphism is associated with reducing the risk of overall adverse drug reactions, meanwhile, GT haplotype for rs1801133, and rs1801131 polymorphism were marginally associated with increased risk of adverse drug reactions. Conclusion: In conclusion, we have successfully found a panel of pharmacogenetic indicators that have the potential to be valuable in predicting the response to methotrexate treatment in patients with rheumatoid arthritis. Haplotypes for rs1801133 rs1801131 polymorphism are associated with reducing or increasing the risk of MTX adverse drug reactions. It is very important to evaluate patients' haplotypes before starting the therapy program so that we can expect the treatment outcome with the most suitable dose and most tolerable one at the same time.